2016
DOI: 10.1017/s1751731116000094
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat quality of Nellore cattle fed different non-fiber carbohydrates sources associated with crude glycerin

Abstract: Crude glycerin, a potential energy source for ruminant animals, has been evaluated, mainly, in diets with high starch content. However, a limit number of studies have evaluated the inclusion of crude glycerin in low starch diets. This study aimed to evaluate the effects of the association of crude glycerin with corn grain or citrus pulp on carcass traits and meat quality of Nellore bulls ( n = 30, 402 ± 31 kg initial weight). The treatment consisted of: CON = control, without crude glycerin; CG10 = 10% of crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Glycerol can be absorbed at half percentage in the rumen wall and enhance glucose circulation via gluconeogenesis in the liver (Remond et al, 1993). Crude glycerin can replace cereal grains with levels up to 100 g/kg DM of feedlot diets of beef cattle without detrimental effects on performance (Parsons et al, 2009;Mach et al, 2009;Lage et al, 2014) and it potentially enhance unsaturated fatty acid deposition on meat (Carvalho et al, 2014;Eiras et al, 2014;Favaro et al, 2016) We hypothesizes that CG (substrate promoter of lactate-utilizer bacteria) could replace VM (inhibitor of gram-positive lactateproducing bacteria) without impairing rumen fermentation or that combining VM and CG would increment the positive effects on fermentation and promote the growth of bacteria that metabolize lactate. The objective of this study was to evaluate the effect of combining VM (0 or 25 mg/kg DM) and CG (0 or 100 g/kg DM) on fermentation and microbial population of feedlot Nellore cattle.…”
mentioning
confidence: 99%
“…Glycerol can be absorbed at half percentage in the rumen wall and enhance glucose circulation via gluconeogenesis in the liver (Remond et al, 1993). Crude glycerin can replace cereal grains with levels up to 100 g/kg DM of feedlot diets of beef cattle without detrimental effects on performance (Parsons et al, 2009;Mach et al, 2009;Lage et al, 2014) and it potentially enhance unsaturated fatty acid deposition on meat (Carvalho et al, 2014;Eiras et al, 2014;Favaro et al, 2016) We hypothesizes that CG (substrate promoter of lactate-utilizer bacteria) could replace VM (inhibitor of gram-positive lactateproducing bacteria) without impairing rumen fermentation or that combining VM and CG would increment the positive effects on fermentation and promote the growth of bacteria that metabolize lactate. The objective of this study was to evaluate the effect of combining VM (0 or 25 mg/kg DM) and CG (0 or 100 g/kg DM) on fermentation and microbial population of feedlot Nellore cattle.…”
mentioning
confidence: 99%
“…The values of RFT (3 to 6 mm) met the requirements of the Brazilian beef industry. Other studies using CG in feedlot diets have reported similar RFT (Carvalho et al, 2014;Favaro et al, 2016;Ribeiro, Messana, Neto, Fiorentini, & Berchielli, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…In feedlot diets of beef cattle, glycerin levels up to 100 g/kg DM have been used to replace cereal grains, with positive effects on performance of beef cattle (Lage et al, 2014;Mach, Bach, & Devant, 2009;Parsons, Shelor, & Drouillard, 2009). Glycerin has also been demonstrated to enhance unsaturated fatty acid concentration of meat (Carvalho et al, 2014;Eiras et al, 2014;Favaro et al, 2016), possibly due to ruminal lipolysis inhibition (Edwards et al, 2012;Krueger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Carcass and meat traits can be altered in the meat of animals fed with crude glycerin by increasing marbling deposition as a function of glycogenic precursor absorption [66]. The change in these features can also be achieved by increasing unsaturated fatty acid content on meat [63,64,67] possibly due to ruminal lipolysis inhibition [19,68].…”
Section: Effects On Carcass Characteristics and Meat Qualitymentioning
confidence: 99%